Culture of Safety Practices in Patient Care at Dr. Lorenzo P. Ziga Memorial District Hospital - Cestina, Joanna Marie; Alcala, Emerlinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
District hospitals like Dr. Lorenzo P. Ziga Memorial District Hospital face unique challenges in maintaining patient safety amid resource constraints and variable staffing, making a strong safety culture essential for preventing adverse events and promoting accountability. This descriptive quantitative study assessed nurses’ perceptions of safety practices using Donabedian’s Structure-Process-Outcome model and High Reliability Organization theory, surveying 50 nurses via total population sampling with a validated questionnaire featuring Likert-scale and Yes/No items analyzed through frequencies, percentages, and weighted means. Findings revealed a young, contractual workforce (predominantly 20-30 years old, <5 years experience) yet strongly positive### Title Culture of Safety Practices in Patient Care at Dr. Lorenzo P. Ziga Memorial District Hospital: Nurses’ Perceptions and High Reliability Organization Principles. Nurse perceptions of safety culture significantly influence patient outcomes in resource-limited district hospitals, where robust systems for error reporting, communication, and policies mitigate adverse events despite staffing challenges. This descriptive quantitative study assessed nurses’ perceptions of safety practices at Dr. Lorenzo P. Ziga Memorial District Hospital using Donabedian’s Structure-Process-Outcome model and High Reliability Organization theory, surveying 50 nurses via total population sampling with a validated Likert-scale questionnaire on policies, communication, and error reporting. Findings revealed a young workforce (predominantly 20-30 years, contractual employment) rating safety culture strongly positive overall (weighted mean=4.53), with highest scores for non-punitive error reporting (4.65), favorable policy perception (4.48), and solid communication practices (4.45). The hospital demonstrates a strong safety foundation aligned with Just Culture principles, warranting sustained reinforcement of confidential reporting, leadership commitment, and continuous training to maintain High Reliability Organization standards and optimize patient safety